Management of Mosque Management Communication in the Management of Islamic Holidays Commemoration (PHBI) at the Jami' Istiqlal Mosque Palembang - Intan Kusuma Rahmadhani; Henny Yusalia; M. Mifta Farid (Universitas Muhammadiyah Palu, 2026)
This research, entitled